Understanding the Nature of Scientific Enterprise in Light of the Project (2061) Criteria and its Relationship to Some Demographic Variables - Zeitone, Ayesh (Jordan Journal of Educational Sciences, 2013)
The purpose of this study was to investigate the level of understanding of the nature of scientific enterprise (NOSE) among basic and secondary stage science teachers in light of the project (2061) criteria, and its relationship to some selected demographic variables such as: gender, teaching experience, school type, scientific qualification, and specialization. A sample of (87) male and female science teachers was selected and utilized from Amman Education Directorates. To collect data, the nature of scientific enterprise test (32 items) was applied. To answer the seven research questions, one – sample (t) test, t – test for two independent samples, one – way ANOVA, chi – square (χ2) test of independence (2x2), contingency coefficient (C), and effect size were applied. The major findings of the study may be summarized as follows: the level of understanding of the nature of scientific enterprise among science teachers in light of the Project (2061) was very low with mean (9.023) points (28.197%) and standard deviation (2.362). This level was significant (α = 0.05) compared to the acceptable educational level (80.0%) in light of the project (2061) criteria. No significant differences were found in the understanding of the nature of scientific enterprise among science teachers due to the variables: gender, teaching experience, school type, scientific qualification, and specialization. In addition, there was no significant relationship between understanding of the nature of scientific enterprise among science teachers in light of the project (2061) and the previous five demographic and academic variables. The research ended by suggesting several recommendations and further studies related to the nature of scientific enterprise.